THE LITERACY MOVEMENT OF INDONESIAN LANGUAGE LEARNING IN ELEMENTARY SCHOOL - Syahru Ramadhan; Sahril; Syarifuddin (Universitas Islam Negeri Mataram, 2025)
The low literacy skills of students in primary schools are an important concern in an effort to improve the quality of education. The Literacy Movement is expected to improve students' reading, writing, speaking and listening skills which are basic elements in Indonesian language learning. This research uses a qualitative approach with a descriptive research type that aims to describe in depth the phenomena that occur in the field related to the implementation of the Literacy Movement. The data collection methods used were observation, in-depth interviews and documentation. Sources of research data include teachers, grade IV students, and documents related to learning activities at SDN 61 Bima City. The data analysis technique used was descriptive qualitative analysis, in which the collected data was analyzed to describe the effectiveness of literacy implementation. The results showed that the implementation of the literacy movement had a positive impact on improving students' reading creativity as shown by data related to the effectiveness of the implementation of the literacy movement, namely reading, writing, speaking, listening and the literacy environment getting good results. The form of literacy activities implemented at SDN 61 Kota Bima, namely the literacy stage and the use of Augmented Reality technology, succeeded in improving students' literacy skills and had a positive impact on their academic development, as well as creating a more interactive and fun learning environment.